2008
DOI: 10.1016/s0828-282x(08)71028-6
|View full text |Cite
|
Sign up to set email alerts
|

A Canadian context for the Acute Study of Clinical Effectiveness of Nesiritide and Decompensated Heart Failure (ASCEND-HF) trial

Abstract: C ongestive cardiac failure comprises a major public health problem that appears destined to grow substantially over the next decade. This entity is the unhappy, but logical final path for a diverse group of cardiovascular conditions dominated by ischemic heart disease and hypertension, but also populated by valvular and cardiomyopathic disorders. It constitutes a major cause of morbidity and mortality, which in its acute form is associated with an annualized mortality of at least 21% and a high rehospitalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…As a result of genetic substudies of BEST that have provided a wealth of knowledge, bucindolol may be the most auspicious candidate to be approved as a heart failure therapy that incorporates a pharmacogenomic-guided strategy. While genetic information is now routinely being collected in clinical trials worldwide 81,82 , it is not always being actively utilized or opened for exploration, squandering many great opportunities.…”
Section: Future Prospects For Pharmacogenomicsmentioning
confidence: 99%
“…As a result of genetic substudies of BEST that have provided a wealth of knowledge, bucindolol may be the most auspicious candidate to be approved as a heart failure therapy that incorporates a pharmacogenomic-guided strategy. While genetic information is now routinely being collected in clinical trials worldwide 81,82 , it is not always being actively utilized or opened for exploration, squandering many great opportunities.…”
Section: Future Prospects For Pharmacogenomicsmentioning
confidence: 99%
“…Larger randomized, placebo-controlled trials, such as the Acute Study of Clinical Effectiveness of Nesiritide in Decompensated Heart Failure (ASCEND-HF) [62], are required to further elucidate the effect of nesiritide on renal function in patients hospitalized for decompensated heart failure.…”
Section: Blood Pressure and Cardiac Output Managementmentioning
confidence: 99%
“…Although two meta-analyses [42,43] have found that at various doses nesiritide can worsen renal function, many others studies [44][45][46] have found that at low doses it poses no risk to kidney function and in some cases is renal protective. Further analysis of this drug and its effects on promoting or preventing cardiorenal syndrome is being performed in several other studies such as the Acute Study of Clinical Effectiveness of Nesiritide in Decompensated Heart Failure [47]. At the moment, it seems safe to say that at doses between 0.005 and 0.01 mg/ kg/ml, there are no additional risks to renal function, whereas doses between 0.0025 and 0.005 mg/kg/ml without an initial bolus may be cardiorenal protective [25,46,48].…”
Section: Vasodilator Therapymentioning
confidence: 99%